Genetic Analysis and Fine Mapping of the Fire Blight Resistance Locus of Malus ×arnoldiana on Linkage Group 12 Reveal First Candidate Genes - Emeriewen, Ofere Francis; Richter, Klaus; Flachowsky, Henryk; Malnoy, Mickael; Peil, Andreas (Frontiers in Plant Science, 2021)
Malus ×arnoldiana accession MAL0004 has been found to be resistant to moderately and highly virulent strains of the fire blight causal pathogen – the Gram-negative bacterium, Erwinia amylovora. Genetic analyses with an F1 segregating population derived from crossing the highly susceptible apple cultivar ‘Idared’ and MAL0004 led to the detection and mapping of the fire blight resistance locus of M. ×arnoldiana to linkage group (LG)12 (FB_Mar12). FB_Mar12 mapped at the distal end of LG12 below the apple SSR Hi07f01 in an interval of approximately 6 cM (Centimorgan), where both the fire blight resistance loci of M. floribunda 821 and ‘Evereste’ map. We fine mapped the region containing FB_Mar12 using 892 progenies. Mining of the region of interest (ROI) on the 'Golden Delicious' doubled haploid genome (GDDH13) revealed 2.3 Mb (megabases) in the homologous region. Of 40 primer pairs designed within this region, 20 were polymorphic and nine were mapped leading to the identification of 24 significant recombinant individuals whose phenotypes were informative in determining the precise position of the locus within a 0.57 cM interval. Analyses of tightly linked marker sequences on the M. baccata draft genome revealed scaffolds of interest putatively harbouring the resistance loci of M. ×arnoldiana, a hybrid between M. baccata and M. floribunda. Open reading frame (ORF) analyses led to the prediction of first fire blight resistance candidate genes with serine/threonine kinase and leucine-rich repeat domains, including homologs of previously identified ‘Evereste’ candidate genes. We discuss the implications of these results on breeding for resistance to fire blight.